2020
DOI: 10.3390/ijerph17186895
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare at Your Fingertips: The Acceptance and Adoption of Mobile Medical Treatment Services among Chinese Users

Abstract: Mobile health (mHealth) services have recently been receiving increasing attention. However, there is a lack of knowledge about how users accept and adopt mobile medical treatment (MMT) services, some of the most promising mHealth services that aim to extend the patient–physician relationship beyond the conventional clinic environment. To fill this research gap, this study proposes a research model for predicting consumers’ acceptance behavior toward MMT services based on the Technology Acceptance Model (TAM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 65 publications
4
37
0
1
Order By: Relevance
“…The study by Luciano, Mahmood, and Mansouri Rad (2020) confirmed that telemedicine adoption is influenced by policies, culture and security and privacy. Li (2020) emphasized on perceived interactivity, perceived personalization and privacy concerns and confirmed that these have significant impacts on users' perceptions of ease of use, usefulness and trust towards mobile medical treatment services. Dhagarra et al (2020) propounded that health care is not only a universally used and complex phenomenon but also very personalized and expensive service, and hence, building and maintaining trust and ensuring privacy are essential for continued participation of patients in a health care delivery system (Shashi et al, 2020).…”
Section: Theoretical Underpinnings and Literature Reviewmentioning
confidence: 89%
“…The study by Luciano, Mahmood, and Mansouri Rad (2020) confirmed that telemedicine adoption is influenced by policies, culture and security and privacy. Li (2020) emphasized on perceived interactivity, perceived personalization and privacy concerns and confirmed that these have significant impacts on users' perceptions of ease of use, usefulness and trust towards mobile medical treatment services. Dhagarra et al (2020) propounded that health care is not only a universally used and complex phenomenon but also very personalized and expensive service, and hence, building and maintaining trust and ensuring privacy are essential for continued participation of patients in a health care delivery system (Shashi et al, 2020).…”
Section: Theoretical Underpinnings and Literature Reviewmentioning
confidence: 89%
“…Results shed light on the fact that the trialability compatibility of mHealth was positively related to the behavioral intention to use. Li [ 41 ] conducted a questionnaire of 303 Chinese users, finding out that the attitude toward using mHealth, trust and technology anxiety are significantly associated with users’ behavioral intention to use mHealth. Lee and Fu [ 42 ] expanded the UTAUT model for an empirical research of users’ mHealth services in Taiwan.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…A total of 58 papers were included (Figure 1; Multimedia Appendix 7), of which 32 papers included adapted or extended existing frameworks. A majority included the Technology Acceptance Model [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] or the Unified Theory of Acceptance and Use of Technology [26,27,[38][39][40][41][42][43]. New frameworks, developed from the review and synthesis of existing frameworks or from empirical research, were proposed by 26 papers [14,15,.…”
Section: Scoping Reviewmentioning
confidence: 99%